Peran Guru dalam Menstimulasi Keterampilan Motorik Halus Anak Kelompok B di TK Bintang Cemerlang Palembang - Sunarti, Giah; Andriani, Dessi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the teacher's role in stimulating the fine motor skills of group B children at Bintang Cemerlang Palembang Kindergarten. In this study, researchers used a qualitative descriptive research method. Collecting data in this study using observation, interviews, and documentation. In analyzing the data, researchers used the data analysis model of Miles and Huberman. The results of the study show that the teacher acts as a guide, facilitator and evaluator. Teachers provide facilities and infrastructure for learning, provide enthusiasm, a place for children to discuss and ask questions and teachers help children create a conducive learning environment.